2023
DOI: 10.3390/ijms24021307
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Causing Apoptosis in a Mouse Model of an Ischemic Spinal Cord Injury

Abstract: A spinal cord injury (SCI) is the devastating trauma associated with functional deterioration due to apoptosis. Most laboratory SCI models are generated by a direct impact on an animal’s spinal cord; however, our model does not involve the direct impact on the spinal cord. Instead, we use a clamp compression to create an ischemia in the descending aortas of mice. Following the success of inducing an ischemic SCI (ISCI), we hypothesized that this model may show apoptosis via an endoplasmic reticulum (ER) stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…GSH, an essential intracellular thiol tripeptide present in mammalian tissues, serves as a critical nucleophilic scavenger and enzyme-catalyzed antioxidant, particularly in response to electrophilic/oxidative tissue damage ( Soni et al, 2023 ). Its deficiency has been implicated in various diseases, including cancer, neurodegenerative diseases, cystic fibrosis, viral infections including HIV-1, respiratory distress syndrome, and aging diseases ( Ruffmann and Wendel, 1991 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GSH, an essential intracellular thiol tripeptide present in mammalian tissues, serves as a critical nucleophilic scavenger and enzyme-catalyzed antioxidant, particularly in response to electrophilic/oxidative tissue damage ( Soni et al, 2023 ). Its deficiency has been implicated in various diseases, including cancer, neurodegenerative diseases, cystic fibrosis, viral infections including HIV-1, respiratory distress syndrome, and aging diseases ( Ruffmann and Wendel, 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, we found that GSH administration reduced the abnormal elevation of NO induced by AHE modeling in the cortex. Furthermore, ER stress can induce apoptosis or inflammation through one or more of the three pathways, mainly including PERK-ATF4, IRE1-XBP1s or ATF6 ( Soni et al, 2023 ). Given the association between iNOS and ER stress-induced apoptosis, we measured ER stress-related genes (ATF4, IRE1α, and ATF6) to further verify the crucial role of iNOS in AHE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation